SISTEM PAKAR PENDIAGNOSA PENYAKIT BERBASIS MOBILE - Maimunah Maimunah; Gagas Pandu Wibowo (CCIT Journal, 2018)
Some of the minor illnesses that often occur in the community are often ignored, if the disease is not treated immediately then the impact will be more severe and serious handling, therefore needed a system that can produce information about the possibility of disease in a person's body, so that can be handled more quickly to avoid dangerous diseases. In this study implemented the expert system to diagnose diseases based on mobile devices as the initial stage for first aid before consultation with the doctor. Therefore, it is necessary to design an expert system of mobile disease-based diagnostics, this system uses mobile technology for easy access and can be done anytime and anywhere, in addition to this system using a simple display that can facilitate the use. In this research, the researcher uses forward chaining method supported from data collection through observation and literature study. By simply selecting the age of the user and selecting the perceived symptoms, the user can immediately know the illness he or she is likely to suffer so that the handling of the disease can be done immediately.